Poważny brak rozeznania oceniającego (kan. 1095, n. 2 KPK) u powoda i wykluczenie przezeń nierozerwalności małżeństwa (kan. 1101 § 2 KPK) w wyroku Roty Rzymskiej c. Erlebach z 21.07.2016 r. - Góralski, Wojciech (Ius Matrimoniale, 2017)
This case concerns a marriage concluded on 13 June 1987 in St. Nichola’s Church San Gemini in Interamnen.-Narnien.-Amerinae diocese, between a 37-years-old Paulus and 27-years-old Maria, who split up several years later. On 22 December 2009 Paulus launched an action for annulment of his marriage before the Tribunal of First Instance, providing exclusion of the indissolubility of marriage and later also lack of discretion of judgement on his side as reasons. On 28 October 2011, the Tribunal passed a pro vincula sentence in both reasons for annulment and the complainant immediately appealed to the Roman Rota. Turnus of the Rota c. Erlebach heard the case in the second instance and, on 21 July 2016, issued a decree of nullity of marriage because of both reasons. When it comes to the lack of discretion of judgement, the complainant’s lack of internal freedom (pathological jealousy and constant fear as well as dependence on his mother) has been observed. When proving the exclusion of the inseparability of marriage, the Tribunal drew attention both to the complainant’s testimony (judicial and non-judicial ones) as well as reasons for simulation and circumstances. The extensive sentences c. Erlebach is of great significance since it indicates the compatibility of two of the above mentioned reasons for nullity: defectus discretionis iudicii and simulatio consensus.